Pressure cycle of superconducting Cs0.8Fe2Se2 : A transport study - Pedrazzini, Pablo; Seyfarth, G.; Jaccard, D.; Pedrazzini, P.; Krzton-Maziopa, A.; Pomjakushina, E.; Conder, K.; Shermadini, Z. (Elsevier, 2011)
Fil: Pedrazzini, P. Comisión Nacional de Energía Atómica. Instituto Balseiro. Laboratorio de Bajas Temperaturas; Argentina